1965
DOI: 10.1111/j.1365-2672.1965.tb02145.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Screening Test for Aflatoxin‐synthesizing Aspergilli of the flavus‐oryzae Group

Abstract: A rapid test for the recognition of aflatoxin‐synthesizing strains of the Aspergillus flavus–oryzae group is described. For this purpose the strains are cultivated on Czapek–Dox agar enriched with an aqueous extract of groundnuts, and in which sodium nitrate is replaced by ammonium chloride. Toxin production is observed by the production of a bright blue fluorescence in the medium when placed under an ultraviolet lamp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Among others, cultivation on coconut agar medium (de Vogel et al 1965;Arseculeratne et al 1969;Lin and Dianese 1976;Davis et al 1987;Abbas et al 2004) has been largely utilized as a preliminary test to detect AF production, by observing the formation of a fluorescent halo around the colony of growing mycelium. Recently, Degola et al (2011) have shown that a liquid formulation of the above-mentioned medium may be used to detect AF by a microplate fluorescent reader-based assay.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, cultivation on coconut agar medium (de Vogel et al 1965;Arseculeratne et al 1969;Lin and Dianese 1976;Davis et al 1987;Abbas et al 2004) has been largely utilized as a preliminary test to detect AF production, by observing the formation of a fluorescent halo around the colony of growing mycelium. Recently, Degola et al (2011) have shown that a liquid formulation of the above-mentioned medium may be used to detect AF by a microplate fluorescent reader-based assay.…”
Section: Introductionmentioning
confidence: 99%
“…radiation have been the subject of research since the 1960s. Early work with natural media used peanuts or coconut in a Czapek-Dox medium with Hyflo-Supercel added to produce a white background (de Iongh et al 1964; de Vogel et al 1965; Arseculeratne et al 1969). Preparation of these media in large volumes is time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Loss or attenuation of aflatoxigenicity by originally highly toxic strains of A.flavus and A . parasiticus has been reported after serial transfers in the laboratory on synthetic and natural substrates for mass transfers (Kulik & Holaday, 1966;DeVogel et al, 1965), single spore isolates (Mayne et al, 1971) and after exposure to barium ions (Lee & Townsley, 1968).…”
Section: Introductionmentioning
confidence: 99%